School 2.0 and the Digital Blackboard: a mercantilization paradigm of the educational system through ICTs - José Luis Murillo García (Revista Electrónica Interuniversitaria de Formación del Profesorado)
We now live in a digital society, fostered and run by a global market, which in turn is managed by multinational corporations and large financial institutions that are creating a new role for education: the school, as an essential element of the economy due to its investments and its importance as a market place for multinationals, but most importantly due to its function in training of a new social class, the “prosumers”. The paradigm of these changes can be clearly seen in the “School 2.0” and its predecessor, the “Digital Balckboard” resources in Aragón (Spain).